LAPAROSCOPIC CHOLECYSTECTOMY: AN EXPERIENCE AT LADY READING HOSPITAL, PESHAWAR - Khan, Nadim; Naeem, Mohammad; Bangash, Adil; Sadiq, Muzaffaruddin; Hamid, Haris (Journal of Ayub Medical College Abbottabad, 2010)
Background: Laparoscopic Cholecystectomy originally a minimal invasive surgical technique involving less hospital stay less economical burden decreased post op complication and early mobility. The objective was to analyse data of patients undergoing laparoscopic cholecystectomy at a surgical setup. Methods: This study was conducted at the Department of Surgery, Lady Reading Hospital, Peshawar from 11th January 2006 till 10th January 2009. Patients aged above 14 year, presenting in the outpatient department with clinical and ultrasonographic evidence of cholecystitis and undergoing laparoscopic cholecystectomy were included in the study. The procedure performed was predominantly the four port technique for laparoscopic cholecystectomy. A proforma was prepared to collect preoperative, operative, and postoperative data. Operative data included the technique used and the difficulties ascertained during those procedures. Data was analysed using SPSS-13.0. Results: Of 421 patients, 387 patients fulfilled the criteria for admission to undergo the procedure. The mean age of all patients was 38.6±7.1 year ranging from 16 years to 72 year with a male to female ratio of 1:8.09. During the first six months 57 patients underwent the procedure for which the mean operating time was 67.4 min. During the last six months the mean operating time was 39.1±8.9 minutes. The overall rate of conversion of laparoscopic cholecystectomy was 6.4%. In comparison the last six months of the study showed one case (1.16%) in 86 patients being converted to open cholecystectomy. The most common cause foe conversion of the laparoscopic procedure to an open cholecystectomy was dense adhesions making dissection of the triangle of Calot’s difficult. In 73 cases (21.4%) the gall bladder was perforated during dissection of gall bladder from the gall bladder bed. Conclusion: The out comes of this study during the last six months is comparable to studies conducted at more experienced centres making laparoscopic more than just an early experience in this part of the world. Keywords: Laparoscopic, Cholecystectomy, Complications, Cholecystitis